I Can Make this Promise - Day, Christine, 1993- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
"When twelve-year-old Edie finds letters and photographs in her attic that change everything she thought she knew about her Native American mother's adoption, she realizes she has a lot to learn about her family's history and her own identity"--
Includes bibliographical references.
Keywords: Identity (Psychology) in children -- Juvenile fiction; Families -- Juvenile fiction -- Washington (State); Family secrets -- Juvenile fiction; Coast Salish Indians -- Juvenile fiction; Indians of North America -- Juvenile fiction -- Washington (State); Adoption -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Identity -- Fiction; Family life -- Fiction -- Washington (State); Secrets -- Fiction; Coast Salish Indians -- Fiction; Indians of North America -- Fiction -- Washington (State); Adoption -- Fiction; Mothers and daughters -- Fiction; JUVENILE FICTION / Family / Adoption; JUVENILE FICTION / People & Places / United States / Native American; JUVENILE FICTION / Social Issues / Prejudice & Racism; Seattle (Wash.) -- Juvenile fiction; Seattle (Wash.) -- Fiction